Trends and Hotspots in Forest Conservation Research: A Bibliometric and Network Analysis from Scopus Data - Judijanto, Loso (West Science Nature and Technology, 2025)
This study presents a comprehensive bibliometric and network analysis of forest conservation research published between 2000 and 2024 using data retrieved from the Scopus database. By employing VOSviewer, the study explores co-authorship networks, country collaborations, keyword co-occurrence, thematic evolution, and research intensity. The findings reveal that forest conservation and forest management are the central pillars of the field, interconnected with emerging themes such as biodiversity, climate change, carbon sequestration, and environmental protection. The analysis highlights key contributors—including influential authors and globally active countries like the United States, Germany, China, and Brazil—while also identifying underrepresented regions in collaborative networks. Temporal overlay mapping shows a shift from traditional forest policy and resource management toward integrative themes aligned with global sustainability agendas. The study concludes that forest conservation research has matured into an interdisciplinary and globally relevant field, yet recommends greater attention to socio-cultural dimensions, equity issues, and increased engagement from scholars in the Global South to ensure inclusive and effective conservation strategies.